Automatic Switch Design with Specified Time Using Wemos D1 Mini Esp 8266 Based on IOT to Save Energy - Moch.Fachruddin Arrazaq; Fendi Achmad (Peneliti.net, 2023)
Excessive use of electronic devices often goes unnoticed. The result of excessive use of electronics is an increase in electricity bills. For that we need a tool that can reduce or limit the use of electricity. The problem that arises in this case is how a tool can operate according to the time needed so that it can limit and save electricity the tool runs as long as needed so that it can limit and save power according to usage Aiming to reduce excessive use of electrical energy, a design tool is designed automatic switch uses IoT-based time, which can turn on and off the switch automatically at a predetermined time, with the aim of saving energy and maximizing cellphones as a means of automatic switching off and Wemos D1 functions as a microcontroller that functions as a wifi reception and its relay. used as a trigger to control the opening and closing of switches and ams modules. 117 as a voltage reducer. The purpose of this tool is to help everyday life by using the tool to reduce electricity bills, thereby reducing the worries of homeowners in the future if the house is left for a very long time.